The Relationship between Parenting Patterns and Sexual Behavior in High School Adolescents in Greater Jakarta Area 2025 - Bunga Romadhona (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2025)
Adolescent sexual behavior has become a critical public health concern in recent years. Limited knowledge of reproductive health may influence adolescents' sexual behavior, highlighting the crucial role of parenting styles in educating and guiding adolescents. Three commonly applied parenting styles are authoritarian, democratic, and permissive. This study aimed to investigate the association between parenting styles and sexual behavior among senior high school adolescents in the Greater Jakarta area (Jabodetabek) in 2025. A cross-sectional approach was employed, involving 100 tenth- and eleventh-grade students selected through stratified area sampling. Data were collected using a structured questionnaire. The Chi-square test, conducted at a 95% confidence level, revealed a statistically significant result (p = 0.000), which was lower than the significance threshold of 0.05. In conclusion, there is a significant association between parenting styles and sexual behavior among senior high school adolescents in Jabodetabek.